2018
DOI: 10.1111/epi.14560
|View full text |Cite
|
Sign up to set email alerts
|

Progressive dissociation of cortical and subcortical network development in children with new‐onset juvenile myoclonic epilepsy

Abstract: Objectives: Structural and functional MRI studies have consistently documented cortical and subcortical abnormalities in patients with Juvenile Myoclonic Epilepsy (JME). However, little is known about how these structural abnormalities emerge from the time of epilepsy onset and how network interactions between and within cortical and subcortical regions may diverge in youth with JME compared to typically developing children. Methods: We examined prospective co-variations of volumetric differences derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
2
11
1
Order By: Relevance
“…Hubs are the regions that provide valuable information about the configuration of a network. 23 All of these studies have consistently documented cortical and subcortical network abnormalities in patients with JME, and this is in line with our present study. One functional connectivity study based on EEG demonstrated an increased delta, theta, alpha1 connectivity and a decreased alpha2 and beta connectivity in the patients with JME as compared to healthy controls, mainly among cortical areas that were involved in sensory-motor integration.…”
Section: Discussionsupporting
confidence: 93%
“…Hubs are the regions that provide valuable information about the configuration of a network. 23 All of these studies have consistently documented cortical and subcortical network abnormalities in patients with JME, and this is in line with our present study. One functional connectivity study based on EEG demonstrated an increased delta, theta, alpha1 connectivity and a decreased alpha2 and beta connectivity in the patients with JME as compared to healthy controls, mainly among cortical areas that were involved in sensory-motor integration.…”
Section: Discussionsupporting
confidence: 93%
“…We previously performed similar analyses in youth with juvenile myoclonic epilepsy (JME), and the results revealed a prospective network characterized by highly correlated cortical regions that were unassociated with subcortical structures. Regarding network hubs, JME participants showed half the total number of hubs compared to controls.…”
Section: Discussionmentioning
confidence: 92%
“…Methods for matrix creation and GT measures can be found in a previous investigation . In short, we calculated a weighted undirected matrix of 85 nodes based on the correlation coefficients of the covariance between nodal volume changes for each group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study concerning structural connectivity showed that patients with JME presented lower modularity indices than healthy controls, indicating weaker modules or communities, demonstrating that JME brains were not developing efficiently. 29 However, no studies focused on the intrinsic thalamic network, and we found new information showing increased modularity of the intrinsic thalamic network in patients with JME.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 70%